Denmark : Selected Issues. (IMF Staff Country Reports; Country Report, 2019)
Considering the Danske Bank case and in the context of a highly integrated Nordic-Baltic financial sector, this Selected Issues paper compares the money laundering (ML) threats and related supervisory vulnerabilities facing the region's largest economies, highlights Denmark's ongoing efforts to address those vulnerabilities, notes critical next steps, and provides recommendations aimed at maintaining the country's current momentum for reform. The paper finds that Denmark has taken important steps to strengthen its anti-money laundering and combating the financing of terrorism (AML/CFT) supervision over the last two years-including via amendments to the AML Act, a significant increase in supervisory resources, and a concomitant increase in on-site inspections-and that these steps represent relevant and necessary responses to the ML risks facing Denmark. The key is therefore to maintain and build on the momentum Denmark has already established. The skills of newly hired inspectors will take time to build, the elaboration of a comprehensive institutional risk assessment model and AML/CFT supervisory manual will take time to complete and strengthened working relationships with foreign counterparts will take time to establish and operationalize.